Participación de la familia y la construcción de la identidad en los niños de la Institución Educativa Inicial N° 454 Mi Casita del Saber, Nauta 2022 - Díaz Vasquez, Belu (2023)
This study was advanced with the intention of arguing the level of the family participation relationship and the construction of the identity of the children of the Initial Educational Institution No. 454 "Mi Casita del Saber" Nauta 2022. This research used as a method and observation instrument. He also used expert judgment to test his instruments before conducting his study. The research considered a broad population that included students, parents and children of the educational institution. The study found a high and direct correlation between the construction of children's identities and the involvement of their families in the Initial Educational Institution No. 454 “Mi Casita del Saber” Nauta 2022”. Pearson's coefficient, or r, was 0.001, indicating a significant relationship.